2020
DOI: 10.1111/jir.12756
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and reliability of the Assessing Levels of Physical Activity health‐related fitness test battery in adults with intellectual disabilities

Abstract: BackgroundPeople with intellectual disabilities (ID) seem to have a lower physical fitness (PF) than their peers without disabilities which coincides with reduced autonomy, life expectancy and quality of life. To assess PF in these individuals, it is necessary to use appropriate tools that permit the assessment of their physical capacities taking into account their specific characteristics. The aim of this work is to study the feasibility and reliability of the Alpha-Fit test battery for adults in a group of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…This is perhaps not surprising, given that each of these tests have demonstrated good feasibility and reliability in other study groups [22,34]. For example, prior studies have demonstrated good feasibility and reliability for BMI among children without disabilities [35] as well as those with intellectual disabilities [27,28], whereas the grip strength test has been shown to have good reliability and feasibility for people with intellectual disabilities [27,28], bipolar disorder [36], and down syndrome [37]. The reliability coefficients of the standing long jump found in our sample (ICC = 0.89) are comparable with those in typically developing children [38], adolescents with an intellectual disability [21], and adults with bipolar disorder [36].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This is perhaps not surprising, given that each of these tests have demonstrated good feasibility and reliability in other study groups [22,34]. For example, prior studies have demonstrated good feasibility and reliability for BMI among children without disabilities [35] as well as those with intellectual disabilities [27,28], whereas the grip strength test has been shown to have good reliability and feasibility for people with intellectual disabilities [27,28], bipolar disorder [36], and down syndrome [37]. The reliability coefficients of the standing long jump found in our sample (ICC = 0.89) are comparable with those in typically developing children [38], adolescents with an intellectual disability [21], and adults with bipolar disorder [36].…”
Section: Discussionmentioning
confidence: 92%
“…Firstly, the one leg stand test, which was used to measure bal-ance ability, demonstrated weak reliability among our sample (ICC = 0.36, SEM% = 107.9%, MDC% = 299.2%). A recent study also found this test unreliable in people with intellectual disabilities [28]. Theoretically, balance is closely associated with the sensory system, particularly vision and hearing [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los plots de Bland-Altman el 0 se establece como valor de referencia. Esto es así porque si la diferencia entre una puntuación en el pretest y en el postest es 0, es que la repetibilidad de la medida es perfecta (Cabeza-Ruiz, et al, 2020). En el presente estudio, el primero de los aspectos a señalar es que en la figura 2.A.…”
Section: Discussionunclassified
“…Adolescents with intellectual disabilities (ID) exhibit relatively unstable and variable movement characteristics. Their motor impairments include deficiencies in the aspects of motor control, such as coordination, reaction time, agility, balance control, muscle strength, and endurance, and they may exhibit comorbidities such as attention deficit hyperactivity disorders or developmental coordination disorders [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Consequently, they are less fit than the typically developing (TD) peers and often have difficulties engaging in movements such as walking and running [ 1 , 2 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%